Walisongo's Concept of Religious Moderation in the History of Islamization of Java in the 15th Century AD - Maulana, Wildhan Ichza (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This research offers a review of the concept of Walisongo's religious moderation. As for mapping the concept of religious moderation in Walisongo comprehensively, four indicators of moderation of the Ministry of Religion of the Republic of Indonesia are used as an analytical tool, including national commitment, tolerance, anti-violence, and accommodativeness to local culture. This research is descriptive qualitative research using the historical method. Meanwhile, primary data sources were obtained from the book